Frequency analysis of time series by polynomials orthogonal on the grid - Sharapudinov, T. I.; Luguev, T. S. (Pattern recognition and image analysis, 2009)
The problem of finding periodic components in a given time series is examined. Our approach to the harmonic analysis is based on the integrated method resting on discrete transforms that employ orthogonal polynomials and trigonometric systems.